COVID – 19 AT UNIVERSITY: SEEING THE INFLUENCE TRANSACTIONAL LEADERSHIP AND LEADERSHIP TRANSFORMATIONAL ON LECTURER PERFORMANCE THROUGH JOB SATISFACTION - Said Almaududi; Albetris Albetris (JURNAL MANAJEMEN DAN BISNIS, 2021)
Job satisfaction and lecturer performance are increasing because of the role of transactional and transformational leadership. The purpose of this study is to examine and analyze the influence of these two leadership styles at Batanghari University with the main focus of study on Human Resource Management. This study uses a survey design in the form of verification research. The sampling design used in this study was stratified random. From all lecturers at Batanghari University, 100 respondents were taken as samples from the Faculty of Economics. Data obtained from questionnaires were collected and analyzed using PLS